2015
DOI: 10.1111/jeb.12557
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical behaviour, habitat use and species size differences shape evolutionary outcomes of hybridization in a coral reef fish

Abstract: Keywords:Amphiprion leucokranos; asymmetric behavioural isolation; reproductive barrier; size-based hierarchy; unidirectional introgression. AbstractHybridization is an important evolutionary process, with ecological and behavioural factors influencing gene exchange between hybrids and parent species. Patterns of hybridization in anemonefishes may result from living in highly specialized habitats and breeding status regulated by size-based hierarchal social groups. Here, morphological, ecological and genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 112 publications
(122 reference statements)
3
52
0
Order By: Relevance
“…However, this hypothesis is unlikely in damselfishes which lay demersal eggs (Gainsford et al . ) as do A. sexfasciatus and A. vaigiensis . Relative differences in population density may also favour hybridization.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, this hypothesis is unlikely in damselfishes which lay demersal eggs (Gainsford et al . ) as do A. sexfasciatus and A. vaigiensis . Relative differences in population density may also favour hybridization.…”
Section: Discussionmentioning
confidence: 91%
“…Two species that form heterospecific social groups and have synchronized spawning seasons may experience external fertilization accidentally involving gametes of both species. However, this hypothesis is unlikely in damselfishes which lay demersal eggs (Gainsford et al 2015) as do A. sexfasciatus and A. vaigiensis. Relative differences in population density may also favour hybridization.…”
Section: Causes Of Interspecific Gene Flowmentioning
confidence: 99%
“…; Gaither et al . ). Overall, this study represents a substantial increase in the number of specimens and genomic resources available for H. maculicauda and H. flaviguttatum .…”
Section: Introductionmentioning
confidence: 97%
“…However, recent studies have found evidence of hybridization and introgression in several marine fishes (Arnold & Fogarty 2009;Richards & Hobbs 2015). In coral reef fishes, examples include butterflyfishes (Pyle & Randall 1994;Montanari et al 2012), anemonefishes (Litsios & Salamin 2014;Gainsford et al 2015), grunts (Rocha et al 2008;Bernardi et al 2013), hamlets (Puebla et al 2007(Puebla et al , 2014, angelfishes (Schultz et al 2006;Gaither et al 2014), surgeonfishes (DiBattista et al 2011, wrasses (Pyle & Randall 1994;Yaakub et al 2007), groupers (Harrison et al 2014;Payet et al 2016) and damselfishes (Coleman et al 2014). Further, hotspots of hybridization have been found in the boundaries of marine biogeographic provinces.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring hybrids among coral reef fishes were once thought to be rare (Hubbs, 1955), although recent studies have identified over 75 species of coral reef fish that hybridize in the wild (Montanari, Hobbs, Pratchett, & van Herwerden, 2016;Yaakub, Bellwood, Herwerden, & Walsh, 2006) and many more cases of natural hybridization continue to be described (e.g., DiBattista et al, 2016;Gainsford, Van Herwerden, & Jones, 2015;Hobbs, Frisch, Allen, & van Herwerden, 2009;Marie, Van Herwerden, Choat, & Hobbs, 2007;Montanari, van Herwerden, Pratchett, Hobbs, & Fugedi, 2012;Payet et al, 2016). Most of these studies have been conducted in well-known suture zones, where biogeographic regions collide and numerical disparity between parent species can result in accidental hybridization (DiBattista et al, 2015;Richards & Hobbs, 2015).…”
mentioning
confidence: 99%